Penggunaan H-Zeolit dan Tawas dalam Pemurnian Crude Glycerol dengan Proses Adsorpsi dan Koagulasi - Isalmi Aziz; Nur Hijjah Bayani Fadhilah; Hendrawati Hendrawati (Jurnal Kimia Valensi, 2017)
Production of biodiesel from used cooking oil byproducts such as crude glycerol with low purity. The crude glycerol containing compounds impurities such as free fatty acids, alcohol, soap, catalyst and water. Compound adsorption of impurities can be done with the H-zeolite as adsorbent, but the resulting quality is still not good. To improve its quality, this research was added alum (coagulation) process so that the adsorption of colloidal-sized compound impurities which can be separated from the glycerol. The purpose of this research is determine optimal condition of adsorption and coagulation impurity compounds of crude glycerol by using H-zeolite and  alum and  also determine quality of glycerol  was obtained. First, crude glycerol acidified by phosphoric acid 85% (pure analysis) until desired pH ±2.5. It was obtained purity of glycerol 72.797%. The next process is adsorption with activated H-zeolite and it obtained purity of glycerol 77.079%. The last process in this research is adsorption and coagulation by using H-zeolite and alum. The highest purity glycerol 93.803% was obtained from condition of adsorption and coagulation for 75 minutes; alum’s concentration 80 ppm; and temperature 60 ºC. The glycerol discharged from adsorption and coagulation process by using H-zeolite and alum is qualify Indonesia National Standard number 06-1564-1995 with 3.512% water content; 2.438% ash content; 0.247% MONG content; has no sugar; 1.259 g/mL density of glycerol; 0.2356% potassium content and 0.0410% aluminium content; and brighter color.DOI: http://dx.doi.org/10.15408/jkv.v0i0.5143